INTEGRATING ARTIFICIAL INTELLIGENCE AND DIGITAL TECHNOLOGY IN CONTEMPORARY PROJECT MANAGEMENT: Evolution of Data-Based Decision-Making Systems - Romualdus Turu Putra Maro Djanggo; Adi Maulana Rachman; Zahania Suhendi Zahra (AIBPM Publisher, 2026)
ABSTRACTThis study examines the integration of artificial intelligence (AI) and digital technology in contemporary project management practices, focusing on the evolution of data-based decision-making systems. The rapid digital transformation has shifted project management paradigms from traditional approaches toward more adaptive and predictive data-driven models. This article employs a systematic literature review method, analyzing 45 international journal articles published between 2015–2024 from Scopus, Web of Science, and Google Scholar databases. The findings reveal that AI implementation in project management significantly improves cost and schedule estimation accuracy by up to 34%, reduces project delay risk by 28%, and enhances resource allocation efficiency by 41%. Machine learning and predictive analytics prove to be the most critical components in supporting more accurate and real-time decision-making. Nevertheless, the adoption of these technologies still faces challenges including limited digital infrastructure, organizational resistance, and human resource competency gaps. This research contributes a conceptual framework for AI integration in the project lifecycle that can serve as a reference for practitioners and academics. Keywords: Artificial Intelligence (AI), Project Management, Digital Transformation, Data-Driven Decision Making, Machine Learning, Predictive Analytics.